PEMULIHAN PONDOK DAUD DALAM KISAH PARA RASUL - George Rudi Hartono Pasaribu; Steven; Andreas Eko Nugroho (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
The Tabernacle of David is the name given to the tent that King David erected on Mount Zion in Jerusalem as a place to place the Ark of the Covenant. It became the center of a new order of joyful worship in stark contrast to the solemn worship at the Tabernacle of Moses. Instead of animal sacrifices, the sacrifices offered at the Tabernacle of David were sacrifices of praise, joy, and thanksgiving (Psalm 95:2,100:4, 141:2). The Tabernacle of David is a type of Church worship. Jesus fulfilled the Old Testament sacrificial system by His death on the cross (Hebrews 1:3, 7:27, 9:12, 9:24-28). The sacrifice of the Church, the New Testament priesthood, is a sacrifice of praise, joy and thanksgiving (Hebrews 13:15, 1 Peter 2:9). This article parses the words of James at the Church Council in Jerusalem in Acts 15:13-18; To show that the salvation of the Gentiles was a fulfillment of Old Testament prophecy, and that they lived during the restoration of the Tabernacle of David. The Apostles knew that the Church was the restored Tabernacle of David, the place where Christ was worshiped, spoke prophetically and walked in His authority. The result of the Church flowing in “School of David” worship, prophecy and authority is a great harvest of souls.